The Reliability of Contralateral Suppression of Otoacoustic Emissions Is Greater in Women than in Men - W. Wiktor Jedrzejczak; Edyta Pilka; Malgorzata Pastucha; Krzysztof Kochanek; Henryk Skarzynski (Audiology Research, 2022)
The aim of this study was to compare the reliability of the medial olivocochlear reflex (MOCR) between men and women. The strength of the MOCR was measured in terms of the suppression of transiently evoked otoacoustic emissions (TEOAEs) by contralateral acoustic stimulation (CAS). The difference between TEOAEs with and without CAS (white noise) was calculated as raw decibel TEOAE suppression as well as normalized TEOAE suppression expressed in percent. In each subject, sets of measurements were performed twice. Reliability was evaluated by calculating the intraclass correlation coefficient, the standard error of measurement, and the minimum detectable change (MDC). The study included 40 normally hearing subjects (20 men; 20 women). The estimates of MOCR for both genders were similar. Nevertheless, the reliability of the MOCR was poorer in men, with an MDC around twice that of women. This can be only partially attributed to slightly lower signal-to-noise ratios (SNRs) in men, since we used strict procedures calling for high SNRs (around 20 dB on average). Furthermore, even when we compared subgroups with similar SNRs, there was still lower MOCR reliability in men.